Albania : Technical Assistance Report-Medium-Term Revenue Strategy; Revenue Administration Reform Options. (IMF Staff Country Reports; Country Report ;, 2022)
Albania is formulating a Medium-Term Revenue Strategy (MTRS) with IMF support. The decision to commit to the development of an MTRS was taken against the background of revenue persistently falling short of budget projections, revenue continuing to lag behind regional peers in tax to Gross Domestic Product (GDP) ratios and the Government's assessment that an increase of revenue of 2.2 - 3.0 percent of GDP will be required to finance its additional spending needs over the next five years.